2008
DOI: 10.1111/j.1365-2575.2008.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship‐based e‐commerce: theory and evidence from China

Abstract: Electronic commerce models and prescriptions from rule-based market economies like the United States have limited applicability in emerging markets. This paper adopts a strategic management perspective to examine the distinctive challenges facing e-commerce in China. A theory is developed to explain how the lack of dependable rules encourages guanxi and relationship-based commerce. It suggests that personal trust, contextual and informal information, and blurred boundaries between business and government have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
164
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(175 citation statements)
references
References 40 publications
5
164
2
4
Order By: Relevance
“…This is consistent with the findings of Martinson's (2008) theory and evidence which found that institutional factors such as socio-cultural factors are not significant to factor hindering adoption of technology. English Language proficiency is one of the socio-cultural factors investigated as a hindrance to e-commerce adoption and was seen insignificant to this study.…”
Section: Hypothesis 3: Socio-cultural Factors Hinder E-commerce Adoptionsupporting
confidence: 81%
“…This is consistent with the findings of Martinson's (2008) theory and evidence which found that institutional factors such as socio-cultural factors are not significant to factor hindering adoption of technology. English Language proficiency is one of the socio-cultural factors investigated as a hindrance to e-commerce adoption and was seen insignificant to this study.…”
Section: Hypothesis 3: Socio-cultural Factors Hinder E-commerce Adoptionsupporting
confidence: 81%
“…This minority contends China's heavily relationship-based and informal society discourages dependable rules for economic and governance structuring (Holliday and Yep 2005;Martinsons 2008;Xin and Pearce 1996). As a result, their research tends to focus on the consumer side of the consumer-producer dyad.…”
Section: Background Chinese E-commercementioning
confidence: 99%
“…Although business scholars generally acknowledge China's e-commerce potential while fretting over her e-commerce impediments (Daley 2003;Downing 2006;Martinsons 2008), a minority of them have focused on challenges to China's evolution into a mature e-market (Hussain et al 2007;Wang 2002;Zhang, Bian, and Zhu 2013). This minority contends China's heavily relationship-based and informal society discourages dependable rules for economic and governance structuring (Holliday and Yep 2005;Martinsons 2008;Xin and Pearce 1996).…”
Section: Background Chinese E-commercementioning
confidence: 99%
“…Light"s [3] study indicated ethnic resources as the major factor increasing the entrepreneurial performance of the ethnic community. Some scholars argued that there is distinction between ethnic and personal sources.…”
Section: B Ethnic Resource and Personal Resourcementioning
confidence: 99%